ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA DALAM MEMILIH PERGURUAN TINGGI SWASTA UNIVERSITAS KATOLIK SANTO THOMAS : (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Angkatan 2022) - Sihotang, Helena; Tarigan, Imanuel (Jurnal Manajemen dan Bisnis, 2023)
The purpose of this research is to analyze the factors that influence student decisions in choosing Private Higher Education, Universitas Katolik Santo Thomas. The population of this research are active students at the Universitas Katolik Santo Thomas, Faculty of Economics, Stambuk 2022. The sample used are 100 people. Sampling technique using probability sampling and simple random sampling. While data collection techniques through questionnaires and documentation. Data analysis techniques using SPSS 20.00 for windows software with factor analysis. The variables used are product, price, physical evidence, people, campus promotions, reference groups, motivation, economic circumstances, personal. Test KMO and Barlett test which shows value Kaiser-Mayer-Olkin Meansure of Sampling adequacy (KMO MSA) of 0.871 with a significance value of 0.000 means that the existing variables and samples can be analyzed using factor analysis. All factors researched had an MSA value of > 0.5, meaning that these variables could still be predicted and analyzed further. Furthermore, the extraction value for each variable is above 0.50, meaning that all indicators are considered capable of explaining the factors. The results showed that 2 new factors were formed, namely internal factors and external factors. Internal factors are the dominant factors that have an influence on student decisions in choosing Private Higher Education, Universitas Katolik Santo Thomas.